The Effect of Career Development and Job Satisfaction on Turnover Intention Mediated by Organizational Commitment to Employees of Stikes Guna Bangsa Yogyakarta - Wilda Devy Anjani; Yuni Siswanti; Winarno Winarno (Journal of Business Innovation and Research, 2023)
This study aims to analyze the effect of career development and job satisfaction on turnover intention with the organizational commitment mediating variable. This research is an explanatory research with a survey approach for hypothesis testing. The sampling technique used is Non-probability (saturated sample) which utilizes members of the entire population as the research sample, the total population in this study is 54 employees. The analytical method used in this study is the Structural Equation Modeling (SEM) method using SmartPLS software. The results of this study indicate that career development has a positive and significant effect on turnover intention, job satisfaction has a negative but not significant effect on turnover intention.